Performance of young pigs fed sorghum grain damaged by lesser grain borer or fungal invasion - Dietz, J.C.; Behnke, Keith C.; Deyoe, C.W.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nutritional quality and physical conditions were used to evaluate grain sorghum damaged by either the lesser grain borer Rhyzopertha dominica (F.) or by nontoxin-producing fungi. Experimental treatments were: 1) control 04.0% moisture), 2) lesser grain borer (LGB) (14% moisture with initial infestation of 4.5 adults/lb of grain) and 3) fungal (Fungal) (15.5% moisture). Control grain was used to formulate a 17% crude protein diet. The remaining dietary treatments were formulated by replacing the control grain with the two damaged grains on a weight basis. Forty-five female Yorkshire and 12 crossbred male pigs, with an average initial weight of 22 lb were used in growth (35 days) and metabolism studies, respectively. Results indicated sirnilar average daily gains and digestibilities for the two types of damaged grain when compared with the control. Pigs fed the diet containing the insect-damaged grain showed an 18% poorer feed conversion rate and a 21% higher average daily feed consumption during the 14 to 35-day interval. Throughout the feeding study, the diet containing the fungal-damaged grain sorghum resulted in feed conversion and average daily feed consumption similar to pigs fed the control diet.
Keywords: Swine; Sorghum grain; Grain borer; Fungus